Atmospheric deposition of trace elements to Daya Bay, South China Sea: Fluxes and sources. (February 2018) - Wu, Yunchao; Zhang, Jingping; Ni, Zhixin; Liu, Songlin; Jiang, Zhijian; Huang, Xiaoping
Abstract: This study was conducted from October 2015 to March 2017, with the aim of providing the first data on the fluxes and sources of wet and dry deposition of trace elements (TEs) in Daya Bay, South China Sea. Wet deposition flux of TEs was always preponderant and orders of magnitude higher than that of dry deposition owing to the high rainfall frequency in Daya Bay. The total deposition fluxes of TEs in the target area were higher than in most places worldwide, but at a moderate level within China. Wet deposition was highest in summer and lowest in winter, whereas dry deposition showed an opposite seasonal trend. The main sources of TEs in wet deposition were seasalt/dust, fossil fuel combustion, and crustal sources, and in dry deposition, they were dust/metallurgic, fossil fuel, petrochemical industry and crustal sources. Highlights: The total deposition fluxes of TEs in the target area were higher than most of the places worldwide, but in a moderate level compared with the observations within China. Wet deposition fluxes of TEs were preponderant and were orders of magnitude higher than that of dry deposition. Wet deposition was highest in summer and lowest in winter, while dry deposition showed an opposite seasonal trend. Sources of TEs in wet deposition were mainly from seasalt/dust, fossil fuel combustion, and crustal sources, whereas dust/metallugic mixed, fossil fuel, petrochemical industry and crustal sources were the main sources of TEs in dry deposition.